The Identification of Nurses’ Behaviour Toward Evidence-Based Nursing - Rani Lisa Indra; Bayu Saputra; Sandra Sandra; T. Abdur Rasyid (Comprehensive Health Care, 2023)
Evidence-based nursing is an effort to improve the quality of nursing care by applying research results in carrying out patient care. This is an important issue in efforts to improve the quality of nursing care but its implementation is still very limited. This study aims to identify nurses' behavior (knowledge, attitude, practice) towards evidence-based nursing in one of the government hospitals in Riau Province. This type of research is descriptive with the sample is nurses who served in the surgical inpatient room in one of the government hospitals in Pekanbaru City with a total of 49 people. Data were collected using The Indonesian Version of Evidence-Based Practice Questionnaire. Data were analyzed univariately with frequency distribution and central tendency. The results showed that 75.5% of nurses were female, 76.5% had a nurse education level, 69.4% had no research experience, 57.1% had never attended a seminar/training on EBN. The average knowledge, attitude and practice towards EBN are 75.96; 21.90; and 30.65, respectively. Nurses' behavior towards EBN tends to be good. It is expected that further collaboration between academic nurses and practitioners in implementing EBN and providing continuing education or training related to EBN can improve the knowledge and practice of EBN by nurses. KEYWORDS: Attitude; behavior; evidence-based nursing; knowledge; practice